Mesenchymal stem cells seeded on a human amniotic membrane improve liver regeneration and mouse survival after extended hepatectomy. (5th December 2017) - Despeyroux, Aure; Duret, Cédric; Gondeau, Claire; Perez‐Gracia, Esther; Chuttoo, Lisa; de Boussac, Hugues; Briolotti, Philippe; Bony, Claire; Noël, Danièle; Jorgensen, Christian; Larrey, Dominique; Daujat‐Chavanieu, Martine; et al.
Abstract: Liver failure remains the leading cause of post‐operative mortality after hepatectomy. This study investigated the effect of treatment with allogenic mesenchymal stem cells (MSCs) on survival and liver regeneration 48 hr and 7 days after 80% hepatectomy in C57Bl/6 mice. To optimize their biodistribution, MSCs were grown on acellular human amniotic membranes (HAM) and applied as a patch on the remnant liver. This approach was compared with MSC infusion and HAM patch alone. Hepatectomized mice without any treatment were used as control group. Survival rate was calculated and biological and histopathological parameters were analysed to monitor liver function and regeneration. MSCs grown on HAM retained their ability to proliferate, to differentiate into osteoblasts and adipocytes and to respond to pro‐inflammatory stimuli. Extended hepatectomy (80%) led to liver failure that resulted in death within 72 hr in 76% of mice. MSC infusion showed an early but transitory positive effect on survival. MSC/HAM patches stimulated regeneration and significantly improved survival rate (54% vs. 24% in the control group at 7 days). They also decreased the severity of hepatectomy‐induced steatosis, suggesting a modulation of lipid metabolism in hepatocytes. MSCs were still present on HAM at Days 2 and 7 posthepatectomy. In conclusion, engineered tissue constructs that combine MSCs and HAM improve survival and liver regeneration after 80% hepatectomy in mice. These encouraging results pave the way to potential clinical application.